Levantamento epidemiológico de lesões bucais em idosos nos centros de referência de universidades públicas da Bahia - Souza, Sarah Mascarenhas (2012)
The aging of the population is the one of the greatest challenges for the contemporary public health, especially in countries in development, where it’s occurs in an environment of poverty and with social inequality. The oral health, an integral and inseparable part of the main health of the people, has been relegated to oblivion when discussing about the health of the elderly population. Therefore, knowing the profile of the oral conditions of some of these people helps in developing educational and social programs directed to this age. The study was a transversal nature with data collected from dental records of the UEFS center of oral lesions and on the biopsy records of the Laboratory of Surgical Pathology at UFBA. For this collection, a form was used to evaluate the following variables: sociodemographic conditions, clinical suspicion, histopathology, location and clinical characteristics of the lesion, lifestyle (smoking and alcohol usage) and prosthesis usage. For this statistical analysis was used the prevalence rate as an occurrence measurement and the ratio of the prevalence as a measure of association. This study is presented in the form of two articles. The first article corresponds to transversal study in order to estimate the frequency of the oral lesions, according the clinical and histopathological diagnostic and describe the sociodemographic profile of elderly patients treated at the reference units of oral lesions of public universities in Bahia (UFBA and UEFS) during the period between January/2002 and August/2010. The second article identifies the sociodemographic conditions associated with the oral cancer development in elderly patients in the reference units of oral lesions in UFBA and UEFS. Were identified lesions in 683 elderly people at UEFS while 296 lesions occurred at UFBA. Analyzing the populations was observed female and black skin predominance and the minority of elderly people were retired. About the clinical diagnosis, fibroid and squamous cell carcinomas were more prevalent while in the histopathological diagnosis, squamous cell carcinoma and fibrous hyperplasia were more prevalent. The results identified some sociodemographic conditions risk factors for the occurrence of oral cancer in the elderly: being male, an advanced age and be farmworkers. The results identified certain sociodemographic A prevention policy needs to be implemented to control the oral lesions in Bahia in order to enable the reduction of the incidence of new cases, early diagnosis and appropriate treatment of oral lesions.